Current trends in the classification, abstracting and indexing of media materials in modern libraries (2009)
Libraries are information repositories. It is generally assumed that libraries house information with emphasis on books. Media materials (MM) are information resources that are not given much cognizance when users are seeking information whereas they are veritable primary information bearers of great research significance to academics; and soft contents for recreational purposes. This paper gives a description of these special class of knowledge resources highlighting bibliographic elements of organizing them in the library. It then focuses on how to abstract and index newspaper resources for easy accessibility and retrieval with modern techniques.